Design of a dynamical hybrid observer for pressure swing adsorption processes. (17th August 2017) - Fakhroleslam, Mohammad; Bozorgmehry Boozarjomehry, Ramin; Fatemi, Shohreh
Abstract: As an integral part of a hybrid control system for Pressure Swing Adsorption (PSA) processes, a dynamical hybrid observer is proposed for online reconstruction of the active mode and continuous states of these processes. Hybrid systems feature both continuous and discrete-event dynamics and hence are very suited to describe PSA processes. For estimation of the active mode, a mode observer is designed, and the continuous spatial profiles in each mode are estimated by distributed and decentralized Kalman filters. The proposed hybrid observer has been applied, in silico, for a two-bed, six-step PSA process used for Hydrogen purification. The active mode of the process along with the continuous spatial profiles of its adsorption beds have been estimated quite accurately based on the measured temperatures and pressures at a few points in the process, these measured signals are all noise-corrupted and measured discretely. Highlights: A mode-observer is designed for PSA processes for the first time. A hybrid observer is proposed for complete state estimation of PSA processes. The mode observer employs a reduced-order DES model of the process. The available measurements for the mode observer are discrete-time and noise-corrupted.